Evaluating online learning engagement of nursing students. (September 2021) - Chan, S.L.; Lin, C.C.; Chau, P.H.; Takemura, N.; Fung, J.T.C.
Abstract: Background: Previous studies suggest that increased learning satisfaction may encourage learning engagement in an online learning environment. Objectives: To evaluate the level of learning engagement and its relationship with students' perceived learning satisfaction in an online clinical nursing elective course. Design: A prospective interventional study. Settings: A nursing course was converted to an online format because of the coronavirus disease COVID pandemic. Participants: Part-time post-registration nursing undergraduates enrolled in an elective online clinical course. Methods: Related teaching and learning strategies were deployed in the course using the Community of Inquiry framework. All students who completed the course were invited to complete an online survey that included a validated Online Student Engagement questionnaire (OSE). Pearson's correlations were used to determine the association between perceived learning satisfaction and learning engagement. A logistic regression model was used to explore the associations of gender, age, working experience and perceived learning satisfaction with higher learning engagement. Results: The questionnaires were completed by 56 of 68 students (82%). The Pearson's correlation coefficient between the mean perceived learning satisfaction and OSE scores was 0.75 (p < .001). Twenty-five students (45%) were identified as highly engaged, using a cut-off of ≥3.5 for the mean OSE score. The mean perceived learning satisfaction (SD) score differed significantly between highly engaged and not highly engaged students [4.02 (0.49) vs. 3.27 (0.62), p < .001]. The logistic regression model showed that a greater perceived learning satisfaction [adjusted odds ratio (OR): 17.2, 95% C.I.: 3.46–86.0, p = .001] was associated with an increased likelihood of higher learning engagement, and >1 year of working experience (adjusted OR: 0.11, 95% C.I.: 0.01–0.89, p = .0039) was associated with a decreased likelihood of higher learning engagement. Conclusions: The study findings suggest that perceived learning satisfaction predicts learning engagement among nursing students in this online learning course.